THE LABORATORY PERFORMANCE OF COLD MIX RECYCLING FOAM BITUMEN BASE (CMRFB-BASE) USING LIME FILLER - Hariyadi, Eri Susanto; Atmaja, A. (ASTONJADRO, 2013)
Due to the demand of road infrastructure increases in Indonesia, it needs an alternative technology having economically, effectively and efficiently results. Reused (recycling) the existing old pavement materials may be one solution. It's expected repairing and improving structural capacity of pavement. One of technology that can be used either for repairing or improving the quality of recycling materials is foam bitumen.The objective of this research is to evaluate the characteristics and to know the strength value of cold mix recycling base by foam bitumen using lime filler. This research uses four types variance of foam bitumen, that is 2%, 2,5%, 3% and 3,5%, and two types of lime filler (1% and 1,5%). According laboratory result is got CMRFB-Base strength based on Indirect Tensile Strength (ITS). If the sample with filler 1%, the standard of optimum foam bitumen is 2,5% with ITS dry about 186,34 KPa, ITS soaked about 125,75 Kpa and TSR is 67,49%. Meanwhile, for the sample with the filler 1,5%, the standard of optimum foam bitumen is 2,5% with ITS dry about 207,71 KPa, ITS soaked about 168,17 Kpa and TSR is 80,96%.For the lowest Static Modulus approximately at foam bitumen 3,5% with filler contain 1,5% = 627,54 MPa and filler contain 1% is around 633,08 Mpa. For the highest Static Modulus approximately at foam bitumen 2,5% with filler contain 1,5% is around 1.857,29 MPa and filler contain 1% is around 1.268,62 MPa.